Management in the Education Service : Challenge and Response. - Society of Education Officers (Routledge Library Editions: Management, 2018)
"This book, first published in 1974, will be of special interest to all who are involved in the implementation of educational planning processes. The contributors explore various aspects of educational management and they describe the development of the planning process at the Department of Education and Science, and compare the objectives and programme structure adopted in the Local Education Authorities of Liverpool, Coventry, and Gloucestershire. The views expressed in the book are intended not so much to commend outright the adoption of these approaches by other authorities, as to give a focus to discussion of issues in management education."- Resumé vydavatel